2021
DOI: 10.1111/brv.12693
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the conserved 3′5′ exoribonuclease EXOSC10/Rrp6 during cell division, development and cancer

Abstract: The conserved 3′‐5′ exoribonuclease EXOSC10/Rrp6 processes and degrades RNA, regulates gene expression and participates in DNA double‐strand break repair and control of telomere maintenance via degradation of the telomerase RNA component. EXOSC10/Rrp6 is part of the multimeric nuclear RNA exosome and interacts with numerous proteins. Previous clinical, genetic, biochemical and genomic studies revealed the protein's essential functions in cell division and differentiation, its RNA substrates and its relevance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 198 publications
(277 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that mutations in EXOSC genes are associated with a variety of distinct diseases ( de Amorim et al, 2020 ). It is reported that the expression of EXOSC10 might influence human development and disease progression ( Stuparević et al, 2021 ). However, investigations on the expression, regulation, and prognostic significance of EXOSC10 in HCC are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that mutations in EXOSC genes are associated with a variety of distinct diseases ( de Amorim et al, 2020 ). It is reported that the expression of EXOSC10 might influence human development and disease progression ( Stuparević et al, 2021 ). However, investigations on the expression, regulation, and prognostic significance of EXOSC10 in HCC are still lacking.…”
Section: Discussionmentioning
confidence: 99%